SYSTEM ORDER BY COMMODITY EXCHANGE TRANSACTIONS ON COMPUTER - Richardo G. Thomas; Drs. Eko Hadiyanto (Jurnal Sistem Informasi, 1995)
At this time where the transaction is very important because activities are oftencarried out by someone. Including a growing commodity on the stock. With thesystem orders on the commodities exchange transactions in a computer can processthe transaction data on sales / purchases with a good, accurate and fast.Design a menu that is easily understood, can be used by the consultant without anyspecial education. This system is designed to help people in taking decis ions quickly,accurately and reduce mistakes.By seeing and reading this article, students can learn the process the sale / purchaseon the commodities exchange.